"You Gotta Choose Your Words Carefully": Findings from Interviews with Environmental Health Scientists about Their Research Translation Perceptions and Training Needs. Issue 5 (3rd May 2020) - Altman, Katya; Yelton, Brooks; Hart, Zac; Carson, Margaret; Schandera, Louisa; Kelsey, R. Heath; Porter, Dwayne E.; Friedman, Daniela B.
Abstract : Scientists are trained to communicate research in a technical manner but often lack the skills to communicate scientific findings to the general public. Effective communication and research translation are increasingly important competencies for researchers and have broader benefits to scientists and society. The aim of the study was to assess the perceptions, experiences, and training needs relative to science communication and research translation of project investigators associated with the Center for Oceans and Human Health and Climate Change Interactions at the University of South Carolina. In-depth, semi-structured interviews were conducted with the Center's investigators. Interview transcripts were coded and analyzed for emergent themes related to science communication and research translation. Investigator descriptions of their research varied in length, and researchers mentioned multiple target audiences. Most investigators preferred in-person and written communication channels and felt "comfortable" communicating uncertain findings to the public despite no formal science communication training. Investigators suggested training focused on plain language development for target communities, assessment of audience needs, and formatting research findings for various groups. Working with multiple target audiences that have preferred communication channels necessitates a comprehensive approach to science communication training to enhance two-way communication between scientists and stakeholders.